THE INFLUENCE OF THE USE OF LEAFLET TEACHING MATERIALS TROUGH COOPERATIVE LEARNING MODEL TYPE JIGSAW IN THE MATTER OF HUMAN DEVELOPMENT TO THE RESULT OF STUDENT LEARNING - Nur bita; darlen sikumbang; rini marpaung (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2013)
The observations were performed in the Junior High School  2 Ambarawa , especially the eighth grade, biology shows that subjects regarded as a difficult subject understandable to students. This is because learning takes place in conventional and low interest in reading students' biology textbooks. One effort that can be done to increase reading and student results of learning is through the use of  Leaflet teaching materials types Jigsaw Cooperative Learning Model. This study aims to determine the improvement of student results of learning in the subject matter of human development after being treated with a Leaflet through tipeJigsaw koopertif learning model. The results showed an increase in the average between pretest and posttest values were measured with N-gain in the experimental class at 55.75 is higher than the control class at 46.89. Average of the highest values in the aspect of understanding that is equal to 59.75 while the average low of results of learning in analyzing aspects of 34.2. Average student learning activities in the experimental class higher at 75.53 compared to 68.34 in the control classes. Given these results it can be concluded that the use of instructional materials Leaflets through Jigsaw cooperative learning model type significantly in improving students' junior high school 2 Ambarawa on the subject matter of Human Development. Keywords: Leaflets, Jigsaw, results of learning, human development.